SELF-CONTROL AS A WAY OF SUCCESSFUL ADAPTATION OF STUDENTS TO PROFESSIONAL TRAINING IN HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2010)
The correlation of adaptation and formation of self-control skills of students' educational achievements as a base of learning results and lowering of adaptive period difficulties is being elucidated in the article.
Keywords: adaptation; self-control; educational achievements